2021
DOI: 10.1016/j.epidem.2021.100481
|View full text |Cite
|
Sign up to set email alerts
|

Social contact patterns among employees in 3 U.S. companies during early phases of the COVID-19 pandemic, April to June 2020

Abstract: We measured contact patterns using online diaries for 304 employees of 3 U.S. companies working remotely. The median number of daily contacts was 2 (IQR 1–4); majority were conversation (55 %), occurred at home (64 %) and lasted >4 h (38 %). These data are crucial for modeling outbreak control among the workforces.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
1

Relationship

5
3

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 12 publications
0
28
0
Order By: Relevance
“…Systematic data collected in other countries has helped to explain the interplay between contact patterns and transmission dynamics [3,4], but studies of contact patterns in the U.S. during this period draw primarily from convenience samples which survey unrepresentative segments of the population. [5,6] While some studies have reported on changing contact patterns throughout the COVID-19 pandemic in the U.S. [1], few have reported on differences in contact patterns among key demographic groups. This is particularly important since the burden of the COVID-19 pandemic has disproportionately fallen on low-income and minority populations, with a heavier burden of COVID-19 cases and deaths in low-income and minority populations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Systematic data collected in other countries has helped to explain the interplay between contact patterns and transmission dynamics [3,4], but studies of contact patterns in the U.S. during this period draw primarily from convenience samples which survey unrepresentative segments of the population. [5,6] While some studies have reported on changing contact patterns throughout the COVID-19 pandemic in the U.S. [1], few have reported on differences in contact patterns among key demographic groups. This is particularly important since the burden of the COVID-19 pandemic has disproportionately fallen on low-income and minority populations, with a heavier burden of COVID-19 cases and deaths in low-income and minority populations.…”
Section: Introductionmentioning
confidence: 99%
“…Systematic data collected in other countries has helped to explain the interplay between contact patterns and transmission dynamics [3, 4], but studies of contact patterns in the U.S. during this period draw primarily from convenience samples which survey unrepresentative segments of the population. [5, 6]…”
Section: Introductionmentioning
confidence: 99%
“…Small reductions in household transmission have potential to meaningfully reduce overall cases. On a daily basis, a larger proportion of close proximity human contact occurs within households [36][37][38] rather than in community settings such as schools, nursing homes or large gatherings notorious for superspreading. While households rarely become superspreading locations, the majority of Americans (72%) 39 live with at least one other individual who would be highly exposed to an index household case.…”
Section: Resultsmentioning
confidence: 99%
“…The Pennsylvania COVID-19 Task Force allocation of initial doses was intended to reflect "disease epidemiology and local community factors 9 ." So why send less vaccine to areas with more Black people, given that they tended to have more face-to-face interactions during the pandemic than White people did 52,53 ? Pennsylvania's Phase 1 sought to prioritize "critical populations 29 " for vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…Even from a so-called “race-neutral” perspective 49,50 , where the goal is to reduce overall harm to society as a whole 51 , the racial disparities we have identified cannot be justified. The Pennsylvania COVID-19 Task Force allocation of initial doses was intended to reflect “disease epidemiology and local community factors 9 .” So why send less vaccine to areas with more Black people, given that they tended to have more face-to-face interactions during the pandemic than White people did 52,53 ? Pennsylvania’s Phase 1 sought to prioritize “critical populations 29 ” for vaccination.…”
Section: Discussionmentioning
confidence: 99%